MP-18 The use of Antibiotics in Small-Scale Duck Farm at Mojokerto District, East Java - Nurul Hidayah; Heru Tristiono; Tutik Surjaningdyah; Agus Hardjito; Erry Setyawan; Alfred Kompudu; Ady Harja Sukarno; Erianto Nugroho (Hemera Zoa, 2018)
Duck is a type of commercial poultry, farmed traditionally by herding transiently or intensive farming by the community. In general, the herding duck looks for food at the surface of rice field and from rice stem. The problem often occurred on these herded ducks were feed poisoning because the extensive use of pesticide in rice field, therefore the traditional   farming had become riskier. The careless use of drugs in handling health problems in duck, such as the administration of antibiotics to all livestock within one group. The objective of this study is to identify the use of antibiotic in duck farm.